Creativity : a short and cheerful guide - Cleese, John (2022)
Creativity is usually regarded as a mysterious, rare gift that only a few possess. John Cleese begs to differ, and in this short, immensely practical and often very amusing guide he shows it's a skill that anyone can acquire. Drawing on his lifelong experience as a writer, he shares his insights into the nature of the creative process, and offers advice on how to get your own inventive juices flowing. What do you need to do to get yourself in the right frame of mind? When do you know that you've come up with something that might be worth pursuing? What do you do if you think you've hit a brick wall? Not only does he explain the way your mind works as you search for inspiration, he also shows that, regardless of the task you've set yourself, you can learn to be better at coming up with a promising idea, refining it and knowing when you're ready to act on it. We can all be more creative.
Originally published: London: Hutchinson, 2020.
Keywords: Creative ability; Psychology